Managing Emotions in the Polish Parliament. The Marshal’s Role - Lesiak, Michał (Emocje i polityka. Sceny z życia polskiego parlamentu, 2016)
This paper analyzes actions taken by the Marshals of the Polish Parliament to control the emotions that appear in the parliamentary hall during the meeting and debates. The author has focused on interactional techniques (both formal and informal) used by the marshals to conduct the parliamentary debate in the most effective way. This article aims to analyze techniques, which are at Marshallʼs disposal in order to prevent Parliamentary debates from getting disturbed by emotions.